1994
DOI: 10.1177/875687059401300202
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting the Employment and Retention of Speech-Language Pathologists in Rural Public Schools

Abstract: Rural pubic schools are mandated by federal and state laws to provide all necessary educational services for their constituents including the therapy services rendered by speech-language pathologists (SLP). However, due to extensive competition for these professionals in the last decade, rural public school administrators have experienced considerable difficulty in recruiting and retaining SLPs. The purpose of this investigation was to identify reasons why SLPs employed in rural public schools opt to remain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…Neeley, Diebold and Dickinson (1994) analysed questionnaires completed by 93 speech-language pathologists employed in the north US rural school system for at least 4 years. The aim of their study was to identify why these speech-language pathologists chose to remain employed in that setting.…”
Section: Attrition From Speech-language Pathology Jobs and The Profesmentioning
confidence: 99%
See 2 more Smart Citations
“…Neeley, Diebold and Dickinson (1994) analysed questionnaires completed by 93 speech-language pathologists employed in the north US rural school system for at least 4 years. The aim of their study was to identify why these speech-language pathologists chose to remain employed in that setting.…”
Section: Attrition From Speech-language Pathology Jobs and The Profesmentioning
confidence: 99%
“…These included workplace issues such as management practices (Denham & Shaddock, 2004;Rossiter, 2000a;Saggers et al, 2001), access to professional development (Foster & Harvey, 1996;Neeley et al, 1994;Saggers et al, 2001), workloads (Denham & Shaddock, 2004), caseloads (Foster & Harvey, 1996;Neeley et al, 1994), workplace relationships and support (Denham & Shaddock, 2004;Foster & Harvey, 1996;Neeley et al, 1994), and compensation for the work provided (Foster & Harvey, 1996;Neeley et al, 1994;Saggers et al, 2001). However, the speech-language pathologists in this study identified positive aspects at a professional level that may mitigate these issues when they act as stressors.…”
Section: Major Themes Evident In the Interviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retention and recruitment of teachers and public school personnel is more difficult in rural areas where job satisfaction is reported to be lower than in suburban and urban areas (Bakker & Schaufeli, 2000;Farmer, 1994;Foster & Harvey, 1996;Kniveton, 1991). Special education teachers, school counselors, teachers of deaf students, school occupational therapists, teachers of children with severe learning disabilities, and SLPs working in rural areas have reported higher incidences of stress than their urban counterparts (Fimian et al, 1991;Helge, 1992;Male & May, 1997;McNeil & Jordan, 1994;Minner & Lepich, 1993;Moracco et al, 1984;Neeley et al, 1994;Wisniewski & Gargiulo, 1997).…”
Section: Rural and Urban Schoolsmentioning
confidence: 99%
“…Job stress in educational personnel has detrimental physiological and psychological effects on educators and the students they serve. These job stressors have been reported by general education teachers, special education teachers, school counselors, teachers of the deaf, school speech-language pathologists (SLPs), and administrators (Beer & Beer, 1992;Borg, 1990;Borg & Riding, 1993;Darcy, Kusznikow, & Lester, 1995;Fimian, Lieberman, & Fastenau, 1991;Male & May, 1997;Moracco, Butcke, & McEwen, 1984;Neeley, Diebold, & Dickinson, 1994;Wisniewski & Gargiulo, 1997;Yezzi & Lester, 2000). The negative effects of stress on SLPs working in schools have not received systematic attention in the literature.…”
mentioning
confidence: 99%